Understanding Conversational Programmers: A Perspective from the Software Industry - Chilana, Parmit K.; Singh, Rishabh; Guo, Philip J. (Proceedings of the 34th Conference on Human-Computer Interaction (CHI 2016), 2016)
Recent research suggests that some students learn to program with the goal of becoming conversational programmers: they want to develop programming literacy skills not to write code in the future but mainly to develop conversational skills and communicate better with developers and to improve their marketability. To investigate the existence of such a population of conversational programmers in practice, we surveyed professionals at a large multinational technology company who were not in software development roles. Based on 3151 survey responses from professionals who never or rarely wrote code, we found that a significant number of them (42.6%) had invested in learning programming on the job. While many of these respondents wanted to perform traditional end-user programming tasks (e.g., data analysis), we discovered that two top motivations for learning programming were to improve the efficacy of technical conversations and to acquire marketable skillsets. The main contribution of this work is in empirically establishing the existence and characteristics of conversational programmers in a large software development context.